Heaven is for real : a little boy's astounding story of his trip to heaven and back - Burpo, Todd; Vincent, Lynn (Nashville, Tennessee : Thomas Nelson, 2010)
Presents the story of the four-year old son of a Nebraska pastor who during emergency surgery slips from consciousness and enters heaven.
Someday we'll see
Includes bibliographical references (pages 159-160).
Keywords: Burpo, Colton, -- 1999-; Heaven -- Christianity; Near-death experiences -- Religious aspects -- Christianity